PEMBELAJARAN MORAL MELALUI MOVIE LEARNING “BATTLE OF SURABAYA” PADA SISWA SD - Marwan, Iwan; badrus, moh; Siti Fadhilah, Asna (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2024)
This study aims to describe Moral Learning in the Battle of Surabaya Film in Class V Students at SDN Plosorejo 1, Gampengrejo District, Kediri Regency by Aryanto Yuniawan. Specifically, it includes: 1) What are the values of moral learning in the movie learning “Battle Of Surabaya “and 2) What are the implications of the movie learning “Battle Of Surabaya “for the moral learning of fifth grade students at SDN Plosorejo 1.This type of research is library research (Library Research). The primary data source is the film